ASPECTS OF INTERNET MARKETING IN THE CONTEXT OF MANAGEMENT OF COMPETITIVENESS OF ENTERPRISES IN THE CONDITIONS OF DIGITIZATION (Development Service Industry Management, 2025)
The article examines the issue of ensuring the competitiveness of an enterprise as its ability to win in competition with other business entities for consumers, the market, resources, investments, as well as opportunities for further progress. It is argued that in the modern era of digitalization and digitization, aspects of management and ensuring the competitiveness of enterprises and organizations are acquiring new colors, approaches, and, accordingly, mechanisms and tools. Therefore, aspects of Internet marketing are becoming increasingly relevant. Therefore, aspects of Internet marketing are becoming increasingly relevant. Therefore, the purpose of the study is to generalize and further develop the Internet marketing toolkit in the context of strengthening the competitiveness of enterprises in the context of digital transformation of the economy and society. The conceptual characteristics of Internet marketing are systematized and generalized. The trends of digital transformation of the Ukrainian economy are identified and their impact on the development of enterprises is determined. The features of managing Internet marketing of enterprises during digitalization are revealed. The tools of managing Internet marketing of enterprises are generalized. The methodological principles of forming an Internet marketing system of enterprises are substantiated, taking into account digitalization trends. A methodology for assessing the quality of Internet marketing management of enterprises has been developed. The state and economic prerequisites for the development of enterprises have been studied, their marketing activities and the quality of the Internet marketing system have been assessed. A description of the management of the Internet marketing system of enterprises has been provided.
Keywords: business management; organizational management; competitiveness; digital transformation; digitalization; Internet marketing